2021
DOI: 10.3390/agriculture11020108
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Application of Rice Straw Stabilizes Soil Bacterial Community Composition and Inhibits Clubroot Disease

Abstract: Straw amendment can improve soil properties and is an effective strategy to control soil-borne diseases. However, gramineous straw application to vegetable fields has rarely been studied. In this study, rice straw was added to the field of Chinese cabbage for one or two years (repeated), and Chinese cabbage plant growth, disease occurrence and changes in soil chemical properties were measured. In addition, the bacterial community composition of Chinese cabbage was analyzed using Illumina MiSeq sequencing. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…4-hydroxy benzoic acid has strong allelopathy on rhizosphere microbes, can inhibit the function of root mitochondria [44], promote the growth of pathogens, and lead to the occurrence of soil-borne diseases [45,46]. Studies have found that straw returning well inhibits the soil-borne pathogens, including Fusarium oxysporum [47], Rhizoctonia cerealis [48], Verticillium dahliae Kleb [49], and Plasmodiophora brassicae Woronin [50]. Therefore, it is speculated that straw returning improves the living environment of microbes [51], promotes the proliferation of microbial populations that can use the carbon source 4-hydroxybenzoic acid in the soil to form dominant species, consumes 4-hydroxybenzoic acid in the soil, and alleviates the soil-borne diseases of crops.…”
Section: Discussionmentioning
confidence: 99%
“…4-hydroxy benzoic acid has strong allelopathy on rhizosphere microbes, can inhibit the function of root mitochondria [44], promote the growth of pathogens, and lead to the occurrence of soil-borne diseases [45,46]. Studies have found that straw returning well inhibits the soil-borne pathogens, including Fusarium oxysporum [47], Rhizoctonia cerealis [48], Verticillium dahliae Kleb [49], and Plasmodiophora brassicae Woronin [50]. Therefore, it is speculated that straw returning improves the living environment of microbes [51], promotes the proliferation of microbial populations that can use the carbon source 4-hydroxybenzoic acid in the soil to form dominant species, consumes 4-hydroxybenzoic acid in the soil, and alleviates the soil-borne diseases of crops.…”
Section: Discussionmentioning
confidence: 99%
“…The soil microbiota also contribute to the outcome of the clubroot disease and were therefore studied in more detail. Analyses were done in either one condition [ 41 ], by comparing symptomatic vs. asymptomatic roots in the same field [ 42 ], resistant and susceptible cultivars [ 43 ], rotation patterns [ 44 ], or treatments with fungicides or biocontrol agents [ 45 , 46 , 47 ], and also virulent vs. avirulent pathotypes of P. brassicae on one host [ 48 ]. Only a few “multi-omics” approaches have been carried out, among them hormones and proteomes [ 3 ].…”
Section: What Has Been Compared?mentioning
confidence: 99%
“…Clearly, the soil microbiota had an impact on the outcome of the interaction in the genotypes as well as over time. Other treatments and experimental conditions that resulted in microbiome modifications included different rotation patterns for fields to reduce the clubroot incidence [ 44 ], and various biocontrol trials such as rice straw, which stabilizes the microbiome and reduces clubroot [ 45 ], and the effect of fungicides [ 47 ]. For the latter condition, one would, of course, assume that their application will alter the microbes’ composition, but it is nevertheless necessary to analyze such predictions.…”
Section: Potential Role For the Microbiomementioning
confidence: 99%
“…In addition, exogenous straw application can not only effectively increase soil organic matter but also increase the soil carbon and nitrogen pool, promote changes in the soil microbial community, and improve the field ecosystem [11]. Repeated application of rice straw changed the soil chemical properties and altered the bacterial community composition to suppress the clubroot disease incidence in Chinese cabbage Repeated application of straw inhibited clubroot of Chinese cabbage by altering soil chemical properties and bacterial community composition [12]. Therefore, we aimed to investigate the effects of rice straw amendments on the performance and incidence of clubroot disease of Chinese cabbage through a 3-year consecutive field experiment.…”
Section: Introductionmentioning
confidence: 99%